ANALISIS TINGKAT KERAWANAN LONGSOR LERENG DI DESA SAMUDERA KULON KECAMATAN GUMELAR KABUPATEN BANYUMAS - Iskahar Iskahar; Sulfah Anjarwati; Windi Febriana Sohebah (CIVeng: Jurnal Teknik Sipil dan Lingkungan, 2020)
Samudera Kulon Village is one of the villages in Gumelar Subdistrict, which is an area of high vulnerability to landslides. This study aims to determine how much the level of landslide hazard in Samudera Kulon, Gumelar District. Data is obtained through direct observation in the field and secondary data from various related agencies. Data analysis was carried out to determine the typology of landslide potential zones and determine the classification of the level of vulnerability to landslides.The results of data analysis showed that the landslide hazard level was between 1.74-2.225, so the level of landslide hazard potential in Samudera Kulon Village was moderate